Building and estimating total cost of web based Fraud Detection System in Microsoft Azure Cloud Platform - Gagandeep Kaur, Dr Harsh Kumar (International Journal of Advanced Science and Technology, 2020)
The cloud computing as a booming technology provides a scaled computing resources from individual users to larger sized organizations at economical cost. However there are lot of chances to get increased costs in cloud computation due to unclear knowledge on cloud computing resources in cloud platforms and unrealistic cost estimations. Every business requires unique kind of cloud model and specific resources requirements for its business setup. Analysing and finding best cloud model was considered a harder task while working on real cloud platforms. This paper addresses the difficulties in selecting appropriate cloud resources that needs to be matched to business requirements. We build a web based fraud detection system and estimating its costs in Microsoft Azure cloud platform. The proposed fraud detection system utilizes the Microsoft Azure’ cloud resources for performing operations like analytics and storage..